Stacking nuances modulate the mechanical properties of graphene/SnO2 nanocomposites. (19th March 2021) - Banarouei, Seyed Arman; Yu, Luxia; Jian, Cuiying
Abstract: Due to its superior mechanical properties, graphene is widely used as reinforcement materials in nanocomposites. In this work, a series of indentation simulations was performed, using finite element method, to investigate the mechanical properties of graphene/TiO2 and graphene/SnO2 nanocomposite films. The force–displacement curves obtained from simulations were first compared to analytical results, which demonstrates that with increasing the thicknesses of metal oxide layers, the mechanical responses of nanocomposites exhibit a transition from non-linear behaviors to linear behaviors. Furthermore, consistent with literature works, increasing graphene volume fraction can enhance the Young's modulus of the corresponding heterostructure. Interestingly, this enhancement can be modulated by nuances in stacking orders, i.e. layer arrangements, of nanocomposites. Through analyzing stress and strain distributions, the underlying mechanisms were proposed. Our results reported here provide comprehensive characterizations and understandings on the reinforcement effects of graphene on graphene/metal oxide nanocomposites.